Effect of estrogens on boar sperm capacitation in vitro - Ded Lukas; Dostalova Pavla; Dorosh Andriy; Dvorakova-Hortova Katerina; Peknicova Jana (BMC, 2010)
Abstract Background Mammalian sperm must undergo a series of controlled molecular processes in the female reproductive tract called capacitation before they are capable of penetrating and fertilizing the egg. Capacitation, as a complex biological process, is influenced by many molecular factors, among which steroidal hormone estrogens play their role. Estrogens, present in a high concentration in the female reproductive tract are generally considered as primarily female hormones. However, there is increasing evidence of their important impact on male reproductive parameters. The purpose of this study is to investigate the effect of three natural estrogens such as estrone (E1), 17beta-estradiol (E2) and estriol (E3) as well as the synthetical one, 17alpha-ethynylestradiol (EE2) on boar sperm capacitation in vitro. Methods Boar sperm were capacitated in vitro in presence of estrogens. Capacitation progress in control and experimental samples was analyzed by flow cytometry with the anti-acrosin monoclonal antibody (ACR.2) at selected times of incubation. Sperm samples were analyzed at 120 min of capacitation by CTC (chlortetracycline) assay, immunocytochemistry and flow cytometry with anti-acrosin ACR.2 antibody. Furthermore, sperm samples and capacitating media were analyzed by immunocytochemistry, ELISA with the ACR.2 antibody, and the acrosin activity assay after induced acrosomal reaction (AR). Results Estrogens stimulate sperm capacitation of boar sperm collected from different individuals. The stimulatory effect depends on capacitation time and is highly influenced by differences in the response to estrogens such as E2 by individual animals. Individual estrogens have relatively same effect on capacitation progress. In the boar samples with high estrogen responsiveness, estrogens stimulate the capacitation progress in a concentration-dependent manner. Furthermore, estrogens significantly increase the number of acrosome-reacted sperm after zona pellucida- induced acrosomal reaction. Conclusions We demonstrate here the stimulatory effect of four different estrogens on boar sperm capacitation in vitro. According to our results, there is significant difference in the response to tested estrogens at different capacitation time and among individual animals. In animals with a high response to estrogens, there is a concentration-dependent stimulation of capacitation and individual estrogens have relatively the same effect. Effects of individual estrogens, differences in the response to them by individual animals, their time and concentration-dependent outcomes further contribute to our knowledge about steroidal action in sperm.